2016
DOI: 10.1016/j.athoracsur.2015.06.034
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Postoperative Radiotherapy in Patients With Completely Resected Thymoma: A Meta-Analysis

Abstract: Our results showed that for completely resected thymoma, PORT had no advantage in the overall group of patients but increased OS in the patients with stage II and III thymoma after a complete resection. On the basis of this study, PORT is beneficial in patients with stage II and III patients after a complete resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…COX regression analysis in our study indicated that Masaoka stage III + IV, not‐R0 resection, and recurrence were independent risk prognostic factors, but older age seemed to be a protective factor for recurrence, which was similar to the study by Li . The role of postoperative radiotherapy for thymomas remains controversial . A previous study pointed out that adjuvant radiotherapy within one month after thymectomy may be helpful in controlling postoperative MG, such as decreasing the possibility of POMC and raising the probability of reaching CSR, but no prognostic benefit for thymoma was found .…”
Section: Discussionsupporting
confidence: 85%
“…COX regression analysis in our study indicated that Masaoka stage III + IV, not‐R0 resection, and recurrence were independent risk prognostic factors, but older age seemed to be a protective factor for recurrence, which was similar to the study by Li . The role of postoperative radiotherapy for thymomas remains controversial . A previous study pointed out that adjuvant radiotherapy within one month after thymectomy may be helpful in controlling postoperative MG, such as decreasing the possibility of POMC and raising the probability of reaching CSR, but no prognostic benefit for thymoma was found .…”
Section: Discussionsupporting
confidence: 85%
“…The role of adjuvant RT after complete resection in Masaoka stage II disease is controversial (26). Recently, well powered large sized studies showed increase in OS in Masaoka stage II and III thymoma with adjuvant RT (9,26,27). Radiotherapy planning should be established cautiously in adjuvant setting in terms of benefit versus toxicity, since thymomas grow in close proximity to critical organs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Çoğunluğunu timomalar oluşturmaktadır ve timik karsinomlara nispeten daha iyi prognoza sahiptir (15) .…”
Section: Discussionunclassified
“…Zhou ve ark. 'nın (15) metaanalizinde evre II, III timomada PORT'nin genel sağkalımı arttırdığı, modern RT teknikleri ile bu artışın daha fazla olduğu belirtilmiştir. Tüm bu çalışmalar tedavi kararı vermede yalnızca evrenin yeterli olmadığını, DSÖ sınıfla-ması ve diğer PF'nin de dikkate alınarak uygun tedavi kararı verilebilmesi gerekliliğini göstermektedir.…”
Section: Discussionunclassified